The design of slushflow barriers: Laboratory experiments - Katrín Helga Ágústsdóttir 1994- (2019)
Snow avalanches and slushflows have endangered Icelanders since the settlement,particularly in the northern-, eastern- and north-western part of Iceland, and havecost many human lives. While snow avalanches are usually the main threat, somevillages in the north-west are threatened by slushflows as well and protection mea-sures for these villages must be designed to provide protection against both snowavalanches and slushflows. Slushflows are a saturated mixture of snow and water.Granular flows such as snow avalanches are compressible, while slushflows are morelike waterflows and nearly incompressible. The aim of this thesis is to identify anengineering design that can effectively stop slushflows upstream of a catching dam.Experiments were carried out in a laboratory set-up, using water flowing down aninclined chute to simulate the behaviour of slushflows hitting different types of ob-structions. The experiment tested different upstream angles of impermeable damsboth with and without braking mounds. Also tested were few a boulder barrier de-signs that are known to function well as breakwaters. Video recordings were made,and the footage used for further analysis and measurements to identify the most ef-fective protection. Results indicate that the most effective solution is a steep boulderbarrier with 90°upstream angle with an impermeable back. If such construction isnot considered feasible, the second-best design is a impermeable barrier with >75°upstream angle and at least one row of braking mounds. It was, furthermore, foundthat a dam based on a traditional berm breakwater did not provide an efficientdesign for a catching dam for slushflows. Snjó- og krapaflóð hafa ógnað Íslendingum frá landnámi. Þau eru sérstaklega al-geng á Norðurlandi, Austurlandi og Vestfjörðum og hafa kostað mörg mannslíf.Þrátt fyrir að snjóflóð séu yfirleitt helsta ógnin eru sum þorp á Vestfjörðum einnigsérstaklega útsett fyrir krapaflóðum og því þurfa varnarmannvirki fyrir þessi þorpað veita vörn bæði gegn snjó- og krapaflóðum. ...